2023
DOI: 10.3390/ijms242115724
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Virulence Factors among Staphylococcus lugdunensis Isolates from Orthopedic Infections: Correlation of β-hemolysin, hemolysin III, and slush Genes with Hemolytic Activity and Synergistic Hemolytic Activity

Stefano Ravaioli,
Davide Campoccia,
Rasoul Mirzaei
et al.

Abstract: Staphylococcus lugdunensis is an emerging high-virulent pathogen. Here, the presence and expression of virulence genes (icaA, fbl, vwbl, fbpA, slush A, B and C, and genes of the putative β-hemolysin and hemolysin III) and the ability to induce synergistic hemolytic activity and hemolysis after 24, 48 and 72 h were investigated in a collection of twenty-two S. lugdunensis clinical isolates. The collection of isolates, mainly from implant orthopedic infections, had previously been grouped by ribotyping/dendrogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Hemolysis is considered a virulence factor in pathogens and is typically caused by the action of various protein hemolysins ( Vandenesch et al., 2012 ). Alterations in the expression or deletion of certain virulence genes can lead to varying degrees of hemolytic activity ( Zhu et al., 2017 ; Ravaioli et al., 2023 ). In our study, we compared the genetic sequence of our strain with genes previously reported to induce hemolysis ( Table 1 ).…”
Section: Case Presentationmentioning
confidence: 99%
“…Hemolysis is considered a virulence factor in pathogens and is typically caused by the action of various protein hemolysins ( Vandenesch et al., 2012 ). Alterations in the expression or deletion of certain virulence genes can lead to varying degrees of hemolytic activity ( Zhu et al., 2017 ; Ravaioli et al., 2023 ). In our study, we compared the genetic sequence of our strain with genes previously reported to induce hemolysis ( Table 1 ).…”
Section: Case Presentationmentioning
confidence: 99%